Organ-on-a-chip microengineering for bio-mimicking disease models and revolutionizing drug discovery - Tanvir Ahmed (Biosensors and Bioelectronics: X, 2022)
The core of the drug research and screening processes is predicting the effect of drugs prior to human clinical trials. Due to the 2D cell culture and animal models' poor predictability, the cost of drug discovery is continuously rising. The development of organ-on-a-chip technology, an alternative to traditional preclinical drug testing models, resulted from the intersection of microfabrication & tissue engineering. Preclinical safety and effectiveness testing is improved by the ability of organ-on-a-chip technologies to mimic important human physiological functions necessary for understanding drug effects. Organ-on-a-chip could drastically improve the success rate of the preclinical testing thereby better predicting how the drug will act on the clinical trials. Organ-on-a-chip is a term used to describe a microengineered biomimetic device that mimics the structure and functionality of human tissue. It integrates engineering, cell biology, & biomaterial technologies on a miniature platform. To reflect human physiology in vitro and bridge the gap between in vivo and in vitro data, simplification shouldn't compromise physiological relevance. At this level of organ-on-a-chip technological development, biomedical engineers specializing in device engineering are more important than ever to expedite the transfer of technology from the academic lab bench to specialized product development institutions and an ever-growing market. This review focuses on the recent advancements in the organ-on-a-chip technology and discusses the potential of this technology based on the current available literature.